Analysis and Options for Namibia's Medium-Term Debt Strategy - World Bank (Washington, DC, 2013)
Since gaining its independence 23 years ago, Namibia has established an enviable track record of political stability, prudent macroeconomic policies, moderate growth, poverty reduction, and natural resource conservation. The country has achieved these gains while facing constraints imposed by geography, legacies of apartheid and colonialism, and the challenges of constructing a national government. Daunting challenges remain, however. Namibia suffers from chronic high unemployment, the ravages of HIV/AIDS, and one of the world most skewed distributions of income. The structure of the economy has remained fundamentally unchanged since Independence: minerals and metals make up the majority of exports; the public sector remains the largest employer; and there has been little investment in labor-intensive manufacturing, which in many countries has absorbed low-skilled labor exiting traditional agriculture. This report uses the Medium-Term Debt Management Strategy (MTDS) framework developed by the International Monetary Fund (IMF) and the World Bank to analyze options facing the GRN as it prepares the new Sovereign Debt Management Strategy (SDMS). This framework emphasizes the explicit analysis of relative costs and risks in a debt management strategy, the linkages between the debt strategy and other macroeconomic policies, and the strategy's consistency with debt sustainability. The report opens with a review of the GRN's current debt management strategy, the sources of financing available to the government, and the macroeconomic environment. The report then applies the MTDS analytical tool to analyze costs and risks of alternative debt management strategies that were developed by MOF participants in the November 2012 capacity-building exercise. It also examines domestic debt market development and contingent liabilities arising from government guarantees, two issues of special concern to the GRN. Finally, it discusses institutional arrangements and implementation issues.